Penerapan Senam Ergonomik Terhadap Perubahan Kadar Asam Urat Lansia di Puskesmas Mlati 1 Sleman - Sri Lestari; Erika Dewi Nooratri (Lembaga Pengembangan Kinerja Dosen, 2024)
Gout is a musculoskeletal disease that occurs in the joints due to an increased concentration of uric acid in the blood. Risk factors that can cause high levels of uric acid include age, gender, obesity, purine diet, alcohol, and some medications. Therapies that can be given to the elderly who experience gout include ergonomic exercises. Objective : To determine the effectiveness of applying ergonomic exercise therapy as a non-pharmacological method to reduce high uric acid levels in the elderly. This study used a case study approach with two elderly had high uric acid levels. The intervention was carried out for 2 weeks by giving ergonomic exercises 4 times in 1 week consecutively with a duration of 20 minutes of exercise. There were changes in uric acid levels in both respondents and they decreased. Ergonomic gymnastics is a potential non-pharmacological method in reducing high uric acid levels in the elderly.